ANALISA PENGUJIAN PENGARUH PEMAKAIAN ZAT ADITIF TERHADAP PERFORMANSI MESIN OTTO - Tulus Burhanuddin Sitorus (Jurnal Dinamis, 2009)
In this study the addition of additives for gasoline aims to improve engine performance through the quality of fuel combustion with air so that combustion can take place completely and to reduce emissions. This study also expected to benefit the education and research to know the effect of additives on engine performance. Research methods of testing, data collection and processing of test results data. Test data is processed include torque, power, specific fuel consumption, volumetric efficiency, thermal efficiency and emissions. The results showed that the mixture of gasoline additives (C2:40) has a calorific value of the highest compared with other mixtures, this is due to a change in the composition of the fuel. Increased torque at C1:40 and C2:40, but decreased in C3:40. This is because the heating value of fuel in C3: 40 also decreased. While the power produced is influenced by the torque generated by the engine. For the parameters specific fuel consumption (SFC) in each mixture is lower than usual when using the gasoline engine. At engine speed 3000 rpm and load 25 kg obtained by the use of the lowest fuel. Volumetric efficiency increases slightly with the addition of the additive content in the fuel mixture in which the smallest volumetric efficiency occurs when the engine using gasoline fuel. Thermal efficiency for a mixture of fuel consumption is greater than using gasoline. For the parameters emissions, the use of additives mixed with gasoline to make the percentage levels of CO, unburned hydro carbon(UHC) and CO2 decreased.